2004
DOI: 10.1007/s00040-003-0728-7
|View full text |Cite
|
Sign up to set email alerts
|

Colonial and geographic variations in agonistic behaviour, cuticular hydrocarbons and mtDNA of Italian populations of Reticulitermes lucifugus (Isoptera, Rhinotermitidae)

Abstract: The subterranean termite, Reticulitermes lucifugus (Rossi), is found throughout Italy. The purpose of this study was to assess variations among colonies collected from the north to south of Italy. A multidisciplinary approach was used including behavioral tests, cuticular hydrocarbon analysis and partial sequencing of mitochondrial DNA. Results showed that Italian R. lucifugus populations were moderately aggressive and that aggressive behavior was unrelated to intercolonial geographic distance. Analysis of cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…Clinal variability and temperature are known to affect CHC patterns in termites and may thus be the epigenetic causes of the CHC profile divergences Uva et al 2004a) that are revealed by termite population structure (Vargo et al 2013). It has been suggested that the composition of the intestinal symbiotic fauna has a dramatic effect on intercolonial agonism and thus acts as a recognition cue in Reticulitermes speratus (Matsuura 2001), C. formosanus (Wei et al 2007), and H. mossambicus (Kirchner and Minkley 2003;Minkley et al 2006).…”
Section: The Multifaceted Roles Of Cuticular Hydrocarbons In Recognitionmentioning
confidence: 96%
See 1 more Smart Citation
“…Clinal variability and temperature are known to affect CHC patterns in termites and may thus be the epigenetic causes of the CHC profile divergences Uva et al 2004a) that are revealed by termite population structure (Vargo et al 2013). It has been suggested that the composition of the intestinal symbiotic fauna has a dramatic effect on intercolonial agonism and thus acts as a recognition cue in Reticulitermes speratus (Matsuura 2001), C. formosanus (Wei et al 2007), and H. mossambicus (Kirchner and Minkley 2003;Minkley et al 2006).…”
Section: The Multifaceted Roles Of Cuticular Hydrocarbons In Recognitionmentioning
confidence: 96%
“…Due to the mutual transmission of CHCs, the caste specificity of CHC signatures can influence general colony odor and reflect the actual caste composition of a colony. For instance, having a high proportion of nymphs in a colony can shift the colony's CHC profile, which can thus serve as a cue for the presence of nymphs and influence the acceptance or rejection of non-nestmates (Uva et al 2004a). The different castes of R. flavipes appear to be well differentiated in terms of their relative proportions of different hydrocarbons (soldiers, younger vs. older larval stages, and neotenics) (Darrouzet et al 2014).…”
Section: The Multifaceted Roles Of Cuticular Hydrocarbons In Recognitionmentioning
confidence: 97%
“…These results show that CC play an important role in the nestmate recognition capacity of soldiers towards dealates of the one-piece termite N. chilensis; such role has been repeatedly shown in separate-piece nesting termites e.g. [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 64%
“…[21][22][23][24][25][26][27]. Although this role has not yet been described in one-piece termites, we tested the possible involvement of CC in the interaction of soldiers and dealates of N. chilensis.…”
Section: Introductionmentioning
confidence: 99%
“…50(3): 185~194 (2011) (Howard, 1993;Nelson, 1993), 그 구조가 다양하여 long-chain linear alkanes, alkenes, mono-/ di-/ tri-methyl-branched alkanes 과 같은 100여종의 탄화수소의 화합물로 구성되어 있다 (Nelson et al, 1993). 표피탄화수소는 곤충의 체내에서 합성 이 되어 체벽에 분포하면서 일차적으로 주로 탈수를 방지하고 (Gibbs et al, 2003), 곤충병원성 미생물의 침투로부터 보호하 며 (Blomquist et al, 1987) (Wagner et al, 2000), 동종 간 에도 성별, 연령 또는 계급 (Nelson and Charlet, 2003;Böröczky et al, 2008), 군집 간, 지역, 기후에 따라 다른 종류의 탄화수 소 혹은 함유량의 차이를 보여 서로를 인식하기도 한다 (Uva et al, 2004;Akino, 2006). 더욱이 하나의 개체에서도 촉각, 다 리 등 부위에 따라 조성비가 다르게 분석되기도 하여 화학분 류가 가능하다 (Lee et al, 2003;Böröczky et al, 2008).…”
unclassified